DAMPAK LAYANAN PERBANKAN DIGITAL TERHADAP KINERJA PERBANKAN DI INDONESIA - Ida Ayu Putu Megawati; Ni Nengah Rupadi Kertiriasih (JURNAL LENTERA BISNIS, 2024)
Advances in digital technology encourage the transition from conventional lifestyles to the digital era, one of which is digital banking services. The use of electronic media in financial products is expected to provide faster, easier, and more appropriate services to customer needs (customer experience), and ensure that customers can make transactions independently by paying attention to security aspects. Banking performance can of course also be influenced by the adoption of these digital banking services. This study aims to determine the effect of digital financial services such as electronic money, ATMs, credit cards, SMS banking and internet banking on banking performance in Indonesia in 2021-2023. Using simple linear regression analysis techniques, it can be seen that credit cards and internet banking can have a significant positive effect on banking performance. A positive relationship is also shown by the SMS banking variable but is not significant. Meanwhile, ATMs and e-money show a negative and insignificant effect on banking performance in Indonesia.